Keterlibatan Mahasiswa KKP-DR UIN Mataram Pada Masa Pandemi Covid-19 Dalam Program Pendidikan Dan Kesehatan Di Desa Dasan Tapen, Gerung, Lombok Barat - Muammar Muammar (Jurnal Participative: Jurnal Pengabdian Pada Masyarakat, 2021)
Corona Virus Disease 19 or known as Covid-19 has changed the order of human life in the world. Life that used to feel good has turned into a big disaster. All aspects of life starting from the economic, social, educational and health aspects have turned into a prolonged and abnormal crisis. The abnormality is not to be lamented but must be able to survive and find a solution. This means that everyone must be involved and take part in efforts to minimize the impact caused by Covid-19. One of the government agencies involved for the above purposes is UIN Mataram. The involvement of UIN Mataram here is to direct students to carry out Participatory Work Lectures from Home (KKP-DR). The implementation of the KKP-DR is focused on the education and health aspects. Both aspects are expected that students can be involved to help the government overcome various problems in education and health. In Dasan Tapen Village, Gerung, West Lombok, various efforts were made by students in both aspects. In the field of education, students provide study guidance to school children from elementary to high school levels, while in the health sector, students conduct socialization to prevent the spread of Covid-19.